LAYANAN BIMBINGAN KELOMPOK MELALUI ZOOM MEETING DENGAN TEKNIK SELF MANAGEMENT TERHADAP PROKRASTINASI AKADEMIK SISWA MTS AL-BIDAYAH BANDUNG BARAT - Heni Agustina; Ika Mustika; Ardian Renata Manuardi (IKIP Siliwangi, 2022)
Today's procrastination is a weakness for students. Environmental temptations make students negligent in carrying out their duties. Procrastination has become an obstacle to student learning progress. How to anticipate procrastination through group guidance services through Zoom Meetings with Self Management Techniques at MTs al Bidayah. The research was conducted with a qualitative approach, data collection techniques were carried out by observation, interviews, and documentation. Data processing techniques in the form of data reduction, data presentation, and giving conclusions. The conclusion of the study is that the counselor encourages the counselee to be involved in the group, explains the rules for keeping secrets, creates internal readiness, facilitates to discuss and explore problems. The results of the evaluation showed a change by increasing the obedience of the task. Student responses are positive. The difficulties are students' distrust, family barriers, zoom and signal techniques. Constraints during guidance are counselors who are not categorized as strata 1, counselor communication with the principal, teacher cooperation with counselors, students do not always follow guidance, parents are indifferent to children. Some obstacles are overcome, others require gradual solutions.Keywords: Zoom Meeting, Self Management Technique, Academic Procrastination.